LITERASI DIGITAL DAN HASIL BELAJAR SISWA SMP: PERBANDINGAN GAMBIA DAN INDONESIA - Qoidah, Nikma Nur; Zain, Muhammad Sofyan; Adha, Al Fajri; Lawrenc, Eunic (EduFisika: Jurnal Pendidikan Fisika, 2023)
The purpose of this study was to find out whether there is an effect of digital literacy on student learning outcomes in the subject of natural sciences subject matter of motion at Junior high school 19 Jambi City and Marn International School Gambia. This research method uses a quantitative method with an associative research approach. The research sample was taken using a purposive sampling technique, with 45 class VII students in each school as the sample. Data was collected through the use of questionnaires that measure digital literacy variables and student learning outcomes. The results of this study indicate that the digital literacy level of students in Indonesia and Gambia is in a fairly good category. Likewise, student learning outcomes in the two countries are also in the fairly good category. The normality test and linearity test show that the data is normally and linearly distributed. The regression test shows that there is an effect of digital literacy on student learning outcomes in both schools, with a significance value of less than 0.05.